Conversion of Polypropylene Plastic Waste Into Liquid Fuel with Catalytic Cracking Process Using Al2O3 as Catalyst - Rachmadena, Devi; Faizal, Muhammad; Said, Muhammad (International Journal on Advanced Science, Engineering and Information Technology, 2018)
Approximately 129 million tons of plastic are produced each year, and from that amount, almost entirely produced from petroleum, while the needs on fuel oil (BBM) is continuously increasing, leading to the depletion of oil and gas reserves. However, besides the problem of raw materials derived from petroleum, the use of conventional plastic as packaging material facing various environmental problems, such as cannot be recycled and cannot be degraded naturally by the environment, causing a pile of plastic waste that causes environmental pollution. Thus, it is crucial to find a solution that can solve both problems. One method of processing plastic waste is to convert it into hydrocarbon fuels. Conversion of plastic waste can be done with the catalytic cracking process which is often used because it utilizes a catalyst to reduce the high temperatures used in the thermal cracking process and save on energy consumption. In this research, the raw material that was used was polypropylene in the form of mineral water cups, and the catalyst used was Al2O3. The purpose of this research was to observe the effect of the cracking process’ length of time, catalyst weight (% catalyst) and range of temperature towards the mass, characteristics, and composition of the product. The length of the cracking time was varied into 20, 40 and 60 minutes, while the % catalyst was varied into 4%, 6%, and 8%, and the operating temperature was varied into 150, 200, 300 and 350oC. From the research, the highest mass of liquid product was obtained at the variation of 350oC, 4% of catalyst for 60 minutes, with the value of  87.3 gr, with a total yield of 17.5%. While the characteristics were 0.762 gr/mL for density, 0.778 for Spgr and 50.4 for oAPI Gravity. As for the other products from different variations had lower mass and yield of liquid, but the characteristics were still in gasoline range’s characteristics. Two samples were analyzed by its composition, and although showed the different value of percentage, both also showed that the liquid product was included into gasoline range (C5-C12).